Contrasting effects of interferon gamma and interleukin 4 on responses of human vascular endothelial cells to tumour necrosis factor alpha. - Paleolog, E; Aluri, G; Feldmann, M (1992)
Tumour necrosis factor alpha (TNF-alpha) and interleukin 4 (IL-4) selectively synergise in inducing expression of the mononuclear cell adhesion receptor VCAM-1 (vascular cell adhesion molecule-1) on human umbilical vein endothelial cells (HUVEC), which results in increased adhesiveness of HUVEC for T lymphocytes. This process may be crucial for adherence of circulating lymphocytes prior to their passage from the blood into inflammatory tissues. IL-4 also amplifies production of interleukin 6 (IL-6) and monocyte chemotactic protein-(MCP-1) from TNF-alpha-activated HUVEC. In the present study we demonstrate that IL-4 enhances production of granulocyte-macrophage colony-stimulating factor (GM-CSF) from TNF-alpha-stimulated HUVEC. Moreover, using cultured adult saphenous vein and umbilical artery endothelial cells, we show identical effects of IL-4 on TNF-alpha-induced responses to those observed with endothelial cells of foetal origin. Additionally, we report here that TNF-alpha and interferon gamma (IFN-gamma) synergise in the induction of both the lymphocyte adhesion receptor VCAM-1, and the TNF-alpha-inducible neutrophil adhesion receptor intercellular adhesion molecule-1, on all three endothelial cell types studied. In contrast, we found that GM-CSF secretion by endothelial cells treated with IFN-gamma plus TNF-alpha was markedly decreased when compared to the response induced by TNF-alpha alone. These results suggest that the combined actions of several cytokines, acting sequentially or in concert, may exert differential effects on activation and accumulation of circulating lymphocytes at sites of inflammation.